Genetic variability and trait association studies in gerbera (Gerbera jamesonii) for quantitative traits - Kumar, Rajiv; Deka, Bidyut C; Venugopalan, R (The Indian Journal of Agricultural Sciences, 2012)
A study was conducted during 2008–09 to estimate the variability, heritability, genetic advance and correlation in 17 genotypes of gerbera for 19 quantitative traits. The phenotypic coefficient of variation was found higher than genotypic coefficient of variation for all the traits under study. High (>20%) phenotypic and genotypic coefficient of variation were observed for number of suckers/plant/year. Leaf breadth and number of suckers/plant/year showed high heritability (95.56% and 96.07%, respectively) coupled with high genetic advance as per cent of mean, indicating presence of additive gene action indicated scope of improving these characters through selection. Flower diameter was significant and positively correlated with disc diameter, stalk length, fresh weight of flower head, durability of single flower, and ray floret length both at genotypic and phenotypic levels.